CONTRIBUTION OF FISHERMAN HOUSEHOLD MEMBERS IN INCREASING FISHERMAN HOUSEHOLD INCOME IN KEPENGHULUAN PARIT AMAN, BANGKO DISTRICT, ROKAN HILIR REGENCY RIAU PROVINCE - Sutriani, Nona; Kusai, Kusai; Nugroho, Firman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTThis research was conducted to identify the types of activities or businesses carried out by members of fishing households, both fishery and non-fishery based, analyze fisherman household incomes and analyze the contribution of household members in helping to increase fisherman household income in KepenghuluanParitAman, Bangko District, Rokan Regency. Downstream.the method used in this research is the survey method. The results showed that the business carried out by fishermen households in the KepenghuluanParitAman in the fishery sector were fishermen, fish salters and fish traders, while the non-fishery sector such as food stalls, small shops, tailors, fried food sellers, online shops, food stalls miso, gasoline seller, market service and motorcycle taxi driver. The household income of fishermen in the KepenghuluanParitAman, Bangko District, RokanHilir Regency, Riau Province with an average of Rp. 4,490,755,-. In increasing the household income of fishermen in KepenghuluanParitAman, it can be concluded that the contribution given by fishermen as the head of the family is high (71,28%), the wife's contribution (27,21%) is low, while the contribution of children (1,51%) is low. Keywords: Contribution, income, Kepenghuluan Parit Aman